PFM.25 Assessment of visceral maceration using post-mortem magnetic resonance imaging in fetuses. (9th June 2014) - Addison, S; Arthurs, O; Lally, PJ; Alavi, A; Taylor, AM; Sebire, NJ; Thayyil, S
Abstract : Background: Post-mortem magnetic resonance imaging (PM MRI) is increasingly used as an alternative for perinatal autopsy, however the artefacts related to maceration has not been described. Objective: To compare the severity of maceration assessed by PM MRI with that estimated by histopathology in fetuses. Design/Methods: We performed PM MRI in 75 fetuses using a 1.5 Tesla Siemens Avanto MR scanner (Erlangen, Germany) before conventional autopsy. PM MRI images were reported blinded to the clinical history and autopsy data using a maceration scale of 0–3 for 6 different visceral organs, and then added to make a composite score (0 to 18). The extent of maceration on histopathology was categorised from 1–4 (none to severe). Results: PM MRI maceration score showed a good correlation with the histopathology maceration score (Figure A ), however no relation was seen with the delivery (death) to PM MRI interval. Figure B and C shows PM MRI of fetuses with minimal and extensive maceration, respectively. Conclusions: PM MRI can be used to quantify the extent of maceration in fetuses. The time from delivery to PM MRI did not affect the MRI assessment of maceration if bodies are stored in the mortuary at low temperature.